Tinjauan Filasafat Psikologi: Pendekatan Kritis Habermas Dalam Perkembangan Psikologi Pendidikan - Tihnike, Dona (Sultan Idris Journal of Psychology and Education, 2025)
Education in Indonesia currently faces systemic challenges, such as the dominance of technocratic approaches, inequality of access, and lack of critical awareness in the learning process. This article aims to explore the contribution of the philosophy of educational psychology through Habermas' critical approach in forming a more democratic and emancipatory educational paradigm. The research was conducted using the Systematic Literature Review method of Habermas' works and literature on educational philosophy, educational psychology, and national education policy. The focus of the study is directed at the ontological, epistemological, and axiological dimensions of education, as well as the application of communicative action theory in the learning environment. The results of the study show that Habermas' approach, which emphasizes dialogue, communicative rationality, and emancipation, is relevant in dismantling oppressive power structures in education. The application of this theory is able to create an inclusive and equal educational public space, and encourage active participation of students. This concept is in line with the current direction of Indonesian education, such as Merdeka Belajar, and can strengthen character education and social awareness. In conclusion, the integration of Habermas' critical approach in Indonesian education provides a conceptual and practical foundation for the transformation of the education system towards a humanistic and reflective democratic society.